2018
DOI: 10.1093/sleep/zsy245
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in breast cancer: a prospective observational study

Abstract: STUDY OBJECTIVES-Insomnia in cancer patients is prevalent, persistent and confers risk for physical and psychological disorder. We must better understand how insomnia develops in cancer patients and explore the main contributors to its chronicity so that insomnia management protocols can be integrated more effectively within cancer care. This study monitors the etiology of insomnia in breast cancer patients and identifies risk factors for its persistence. METHODS-173 females with newly diagnosed, non-metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 22 publications
5
53
1
5
Order By: Relevance
“…Over one-fifth of patients with BC presented severe distress symptoms during the COVID-19 outbreak. The scores in our study were significantly higher than patients with BC under normal conditions in previous studies, which showed about only 3.5% patients reported severe anxiety and depression, [17][18][19][20][21] indicating an additional increase of mental stress on the patients with BC by the COVID-19 crisis.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Over one-fifth of patients with BC presented severe distress symptoms during the COVID-19 outbreak. The scores in our study were significantly higher than patients with BC under normal conditions in previous studies, which showed about only 3.5% patients reported severe anxiety and depression, [17][18][19][20][21] indicating an additional increase of mental stress on the patients with BC by the COVID-19 crisis.…”
Section: Discussioncontrasting
confidence: 70%
“…A 4-point Likert scale is used to rate each item (eg, 0 ¼ none, 4 ¼ very severe), yielding a total score ranging from 0 to 28. The total score is interpreted as follows: absent of insomnia (0-7); subthreshold insomnia (8)(9)(10)(11)(12)(13)(14); moderate insomnia (15)(16)(17)(18)(19)(20)(21); and severe insomnia (22)(23)(24)(25)(26)(27)(28). The IES-R, also a self-reported questionnaire, yields a total score (ranging from 0 to 88).…”
Section: Psychological Status Of Patients With Bc During Covid-19mentioning
confidence: 99%
“…Sleep disturbance is a widespread public‐health problem that has a negative impact on quality of life for individuals and represents a serious economic burden for society (Dragioti, Bernfort, Larsson, Gerdle, & Levin, 2017). Approximately 23%–46% of breast cancer survivors (BCS) suffer from an “insomnia disorder,” the most common sleep disorder, which is characterised as persistent difficulty initiating or maintaining sleep with a concomitant waking dysfunction (Fleming et al., 2019). Insomnia has been associated with various factors, such as joint pain, hot flushes, anxiety, depression and fear of recurrence in BCS (Desai et al., 2013; Lowery‐Allison et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The longer time spent awake during the night and the longer time taken to fall asleep observed in fatigued participants, corroborates the higher subjective feeling of insomnia in this study. As a self-report, the ISI was chosen since insomnia is common in cancer survivors reporting having sleep disorders 48 . We found that the majority (83%) of fatigued participants in the present study reported significant sleep disruption (ISI total score > 8), whereas this was reduced to 50% in the non-fatigued group.…”
Section: The Mismatch Between Subjective and Objective Measures Of Sleepmentioning
confidence: 99%